Some Gauge Related Aspects in Gauge Theory - Triyanta Triyanta (Indonesian Journal of Physics, 2008)
Gauge freedom is one important property of gauge theory. It enables one to choose gauge fields that fulfill a certain condition for conveniences. Thus, gauge freedom leads more fruitful and interesting development of gauge theory. In this paper we will discuss some gauge condition related aspects where the generalized gauge is taken into consideration. More attention will be given to the FS gauge.